A novel prognostic factor for hepatocellular carcinoma: protein disulfide isomerase - Yu, Su Jong (The Korean Association of Internal Medicine, 2014)
BACKGROUND/AIMS: Protein disulfide isomerase (PDI) has been implicated in the survival and progression of some cancer cells, by compensating for endoplasmic reticulum stress by upregulating the protein-folding capacity. However, its prognostic role in patients with hepatocellular carcinoma (HCC) has not been investigated. METHODS: We collected HCC tissues from 83 HCC patients who underwent surgical resection for an immunohistochemical study of PDI. Overall survival (OS) was measured from the date of surgical resection until the date of death from any cause. Radiological progression was evaluated using the modified Response Evaluation Criteria in Solid Tumors in an independent radiological assessment. RESULTS: PDI expression was found to be increased in human HCC compared to adjacent nontumor tissues. Increased immunopositivity for PDI was associated with a high Edmondson-Steiner grade (p = 0.028). Univariate analysis of patients who had undergone surgical resection for HCC showed that tumor PDI upregulation is a significant risk factor for poor OS (p = 0.016; hazard ratio [HR], 1.980) and time to progression (TTP; p = 0.007; HR, 1.971). Multivariate analyses revealed that high PDI expression was an independent predictor of a shorter TTP (p = 0.015; HR, 1.865) and poor OS (p = 0.012; HR, 2.069). CONCLUSIONS: Upregulated PDI expression is associated with aggressive clinicopathological features of HCC; thus, PDI might serve as an independent prognostic factor and a potential therapeutic target for HCC patients.